2019
DOI: 10.1002/pssr.201900063
|View full text |Cite
|
Sign up to set email alerts
|

CVD Grown MoS2 Nanoribbons on MoS2 Covered Sapphire(0001) Without Catalysts

Abstract: One‐dimensional (1D) atomically thin crystals have attracted considerable interest due to their unique properties and potential applications. Herein, the chemical vapor deposition (CVD) growth of molybdenum disulfide (MoS2) nanoribbons on sapphire(0001) supported monolayer MoS2 flakes without catalysts as well as the characterizations by means of Raman and photoluminescence (PL) spectroscopy, optical microscopy (OM), atomic force microscopy (AFM), and scanning transmission electron microscopy (STEM). The Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…4 b). It can be confirmed that the crystal axis direction is the (001) direction, which indicates that the sample is composed of multiple layers of 2-D MoS 2 nanoflakes [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…4 b). It can be confirmed that the crystal axis direction is the (001) direction, which indicates that the sample is composed of multiple layers of 2-D MoS 2 nanoflakes [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…[22] Wu et al reported on the growth of MoS 2 nanoribbons on sapphire without catalysts. [23] In the VLS growth, the super-saturated liquid droplets are formed by a sodium chloride reaction with molybdenum oxide (MoO 3 ). [24] Furthermore, the VLS method can be used for 1D growth because 1D nanostructures are favorable during the growth steps from super-saturated catalytic droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al synthesized highly oriented centimeter-scale MoS 2 single crystals using gold foil as the growth substrate [ 31 ]. Li et al prepared wafer-scale MoS 2 single crystals on sapphire substrates through step-induced nucleation [ 10 , 32 ]. However, the triangular domain size of these MoS 2 crystals is only tens of microns, and the cost of the sapphire and gold foil substrates is relatively high.…”
Section: Introductionmentioning
confidence: 99%